(3edcjI GdWHbGJ (B:s (3GdLRA GdChd (B/s - (3NGdO eMeO Rcj UGdMs; (3Jhajb MSf aQLs; (3LGeYI GdGScfOQjIs (3cdjI GdMbhbs ((3GdEScfOQjI(B:s (3cdjI GdMbhb (B- (3LGeYI GdEScfOQjI,s, 1979)
(3Jcef Ggejg edcjg GdWHbGJ ai VQhQg GdScf hGdhSGFd GdeJGMg dGTHGY Jdc GdMGLg gPg GdhSGFd GdJi jecf MUQgG ai GHQGe YbO ef GdYbhO GdJi JQO Ydi GdGfJaGY HGdGTjGA Gh GHQGe YbO ef GdYbhO GdJi JQO Ydi Gdedcjg Gh GdMbhb GdYjfjg GdGNQi hedcjg GdWHbGJ JMbb eUdMg eROhLg ddHGfi hddeMJGL Gdi GdScf agi JMbb eUdMg ddHGfi JXgQ ai JaGOi bjhO JXgQ ai JaGOi bjhO GdGjLGQ GdJi jJSe HgG cd JTQjY jUOQ ai gPG GdTCf hJMbb GjVG eUdMg deMJGL GdScf JJeKd ai JaGOi OaY Ndh GdQLd bHd GdGSJFLGQ hOaY GdGLQg GdeZGdi ajgG ef GjQGOg GdTgQi HUag eSJeQg(B.s
(3QSGFd fSNI efaQOIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdGScfOQjI, cdjI GdMbhb, bSe GdbGfhf GdeOfj (B1979.s
Keywords: (3GdbGfhf GdeOfjs; (3GdfWGb GdeYfhj dedcjI GdSads; (3GdfWGb GdeYfhj dedcjI GdYdhs; (3edcjI GdCLRGAs; (3CMcGe edcjI GdSads; (3Mbhb edGc GdYbGQs; (3edcjI GdWHbGJs; (3GdCLRGA GdeTJQcIs; (3QSGFd LGeYjIs -- (3LGeYI GdGScfOQjIs